Guidelines for Simple Linear Regression Analysis in IBM SPSS: A Step-by-Step Approach - Koirala, Rabin (International Research Journal of MMC, 2025)
Simple linear regression is a powerful statistical tool used for scrutinizing the relationship between an independent variable, and a dependent variable. SPSS, which stands for Statistical Package for the Social Sciences, is a software application developed by International Business Machines Corporation (IBM) for a statistical analysis. This article aims to suggest some guidelines for executing a simple linear regression analysis in SPSS. The author went through books, journal articles and relevant website materials to muster required secondary qualitative data for the attainment of the objective. A comprehensive overview of literature on the regression analysis enables the author to conclude data preparation, assumption validation, data entry in SPSS, simple linear regression analysis, interpretation of the results and reporting of findings as guidelines for conducting simple linear regression analysis. This article is significant as it offers a systematic and accessible framework, aiding researchers and analysts in effectively utilizing SPSS for the accurate and efficient analysis of simple linear regression in empirical research studies.